Pengaruh Tax Planning and Carbon Emission Disclosure Terhadap Nilai Perusahaan Dengan Komisaris Independen Sebagai Pemoderasi - Soetardjo, Mulyadi Noto; Nurmawati, Sukma (Media Riset Akuntansi, Auditing & Informasi, 2024)
This research aims to examine the effects of corporate tax planning and carbon emission disclosure on firm value with an independent board of commissioners as a moderating variable. Firm value is measured using Tobins Q, corporate tax planning using ETR and carbon emission disclosure using an index by Choi et al. (2013). Data is collected using purposive sampling from companies in non- cyclical and cyclical sector for the periods of 2021-2022, resulting in a total sample of 231 firm-years. The result reveals that corporate tax planning has a negative impact on firm value. However, carbon emission disclosure and independent board of commissioners do not influence firm value. In relation to moderation effect, it is found that independent board of commissioners does not strengthen the relationship between corporate tax planning and firm value but it enhances the positive relationship between carbon emission disclosure and firm value. These findings provide insights into how corporate tax planning and carbon emission disclosure practices can affect firm value, with the role of indepenent board of commissioners in moderating these relationships. The implications of this research can assist companies in repositioning and optimizing their tax planning strategies and improving carbon emission disclosures by taking into account the role of independent commissioners of the company.